Development of a friction and wear testing machine; fabrication / Muhammad Ridhwan Sikh Omar - Sikh Omar, Muhammad Ridhwan (2005)
This report is about development of a pin on disc, friction and wear testing machine. For this project purposes, a flat mating surface between the disc and the specimen is focused. The scope of the project are to fabricate a machine where it can hold a brake pad material having a rectangular shape of size 10mm x .10mm with operating speed of 95 rpm with up to 200N load and conducting a friction and wear test in wet condition. This report gives some literature survey about the machine, its advantages and disadvantages over other types, shown technical drawings for each component and complete fabrication in forms of CA TIA and AutoCAD, procedures in conducting friction and wear test in wet condition and also the data analysis. In this report, related information from many sources such as books, websites, catalogs and lecturers (through discussion) about friction and wear are provided.